Effect of Management Systems on Semen Quality of Muscovy Drakes - Etuk, I.F.; Ojewola, G.S.; Nwachukwu, E.N. (International Journal of Poultry Science, 2006)
Semen quality of muscovy drakes was studied in a randomized complete block design (RCBD) under semi-intensive management system (SI), intensive system with wallow (IW) and intensive system without wallow (IO) using 12 active drakes in plot containing 60 female Ducklings. Semen collected by manual massage method 3 times at 5 days intervals beginning from week 33 showed that semen volume, sperm motility and sperm count were significantly higher (P< 0.05) in SI and IW than IO. Semen volume of the drakes under the three management systems ranged from 0.20mls to 0.30mls with IW and IO being the highest (0.30mls) and least (0.20mls) respectively. Drakes reared under IO produced significantly least percent sperm motility (68.58), whereas, those reared under SI (75.42) and IW (76.67) produced significantly higher percent sperm motility. Drakes reared under IO gave the least (95.58 per ml. of ejaculate) sperm count. This is closely followed by drakes reared under IW (107.83) and SI (109.17) respectively. There were no significant differences (P>0.05) in the proportion of normal sperm and semen pH that could be attributed to management systems adopted; but sperm concentration of drakes in the 3 management systems varied significantly (P< 0.05) being 1761.67 x 106/ml (SI), 1801.67 x 106/m (IW) and 1700.00 x 106/ml (IO). In conclusion, availability of Swimming water in the range and wallow contributes positively to the semen quality of Drakes.